The Teaching of Indonesian Culture-Based Speaking Skills Using the Textbook “al-Arabiyah Lil Hayah” - Nur Toifah; Umar Al Faruq (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
This study describes teaching Indonesian culture-based speaking skills using the textbook al-Arabiyah Lil Hayah. This research uses the descriptive qualitative method. At the same time, the data collection techniques in the study were carried out by triangulation techniques which included observation, documentation, and literacy. The implementation of teaching Indonesian culture-based speaking skills is carried out in four ways: 1) in planning, which includes the preparation of a Semester Learning Plan (RPS); 2) in teaching materials, the theme of Arabic speaking skills is integrated with Indonesian culture in a “melting pot”; 3) in the implementation of learning, teachers use several learning methods in turn, including picture and picture, role-playing, communicative, story, discussion, and group work; and 4) in the learning assessment, some assessed aspects are pronunciation, sentence arrangement, clarity of voice, the accuracy of vocabulary, and smoothness.